SISTEM PENDUKUNG KEPUTUSAN UNTUK KELAYAKAN KELANJUTAN PENERIMAAN BEASISWA MENGGUNAKAN METODE ANALYTICAL HIERARCY PROCESS (AHP): Studi Kasus : SMK Padakembang - Mina Ismu Rahayu; Linda Apriyanti (LPPM STMIK BANDUNG, 2020)
One of the programs in vocational Padakembang that help create quality human resources is a scholarship program. In order for scholarship funds channeled to run smoothly it is necessary to evaluate for continued acceptance of the scholarship, so the scholarship is acceptable to truly meet the criteria without prejudice to either party.To help determine the results of the evaluation for the continuing acceptance of the scholarship it takes a decision support system. The method can be used for Decision Support System is to use Hierarcy Analytical Process (AHP). The method chosen because it is a form of decision support models where the main equipment is a functional hierarchy to the main input of human perception, which in this case is a person who is expert in scholarship or people who know trouble of scholarships.